Antagonism and mycoparasitism potential of Trichoderma spp. on some of the major soil borne pathogens of soybean - X.B. YANG, SHRISHAIL S. NAVI, A.H. RAJASAB* and (Indian Phytopathology, 2016)
In an in vitro dual culture plug technique, a single 6-mm culture plug of actively growing cultures of Colletotrichum truncatum, Fusarium virguliforme, Macrophomina phaseolina, Pythium irregulare, Rhizoctonia solani, and Sclerotinia sclerotiorum were placed inverted on one end inside periphery of 9-cm PDA plates and on the opposite end 6-mm culture plug of either Trichoderma hamatum (T1-03) or T. koningiopsis (T2-10). Against Septoria glycines (SG), culture plug of T1-03 or T2-10 were placed in the center of pre-spread SG spore suspension PDA plates. Both T1-03 and T2-10 significantly (P<0.05) suppressed radial growth of pathogens and mycoparasitised target pathogens. SEM processing revealed T1-03 coiled around hyphae of M. phaseolina, P. irregulare, R. solani and S. sclerotiorum, and penetrated hyphae of C. truncatum and P. irregulare. Also, T2-10 encircled hyphae of C. truncatum, M. phaseolina, P. irregulare and R. solani and penetrated the hyphae of M. phaseolina, R. solani and S. sclerotiorum. The area under colony growth of pathogens were significantly (P<0.05) lower in dual culture plates with either T1-03 or T2-10 compared with control plates.